2013
DOI: 10.1002/meet.14505001091
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the query behavior in task‐based collaborative exploratory Web search

Abstract: Collaboration in the information seeking and retrieval environment is common, particularly when the search task is complex and exploratory. Multiple factors such as contextual features and task type can affect users' query behavior. This paper presents a study investigating the effects of collaboration and task types on users' query behavior. The study involves two conditions: collaborative search and individual search, and the two search tasks: the recall‐oriented information‐gathering and the utility‐based d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 25 publications
0
25
2
Order By: Relevance
“…The lack of differences we observed in the traditional information retrieval metrics of precision and recall suggest that studies of collaborative search should consider more than these outcome measures. Collaborative search metrics are still being defined and developed – e.g., (Shah & González‐Ibáñez, ; Yue et al, ) – and additional measures are needed. The behavioral concordance measures we developed were effective in finding interesting effects of awareness, and provide another set of tools for use in understanding collaborative search behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of differences we observed in the traditional information retrieval metrics of precision and recall suggest that studies of collaborative search should consider more than these outcome measures. Collaborative search metrics are still being defined and developed – e.g., (Shah & González‐Ibáñez, ; Yue et al, ) – and additional measures are needed. The behavioral concordance measures we developed were effective in finding interesting effects of awareness, and provide another set of tools for use in understanding collaborative search behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative search metrics are still being defined and developed -e.g., (Shah & González-Ibáñez, 2011;Yue et al, 2013) -and additional measures are needed. The behavioral concordance measures we developed were effective in finding interesting effects of awareness, and provide another set of tools for use in understanding collaborative search behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Kinley, Tjondronegoro, Partridge, and Edwards (2012) found that users needed to reformulate more queries in exploratory tasks requiring high search skills. Yue, Han, and He (2013) found that system types would influence users' query reformulation behavior. Xie and Joo (2012) found that users were more likely to modify their queries when using OPACs than when using search engines.…”
Section: Contextual Factors Influencing Query Reformulationmentioning
confidence: 99%
“…Yue et al (2013) found that users added more new terms in an academic literature search than in a travel information search. For example, found that specialization was observed frequently in simple and hierarchical tasks, whereas substitution was applied more frequently in parallel search tasks.…”
Section: Contextual Factors Influencing Query Reformulationmentioning
confidence: 99%
See 1 more Smart Citation